2007
DOI: 10.1016/j.jnucmat.2007.01.034
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the tokamak size in edge transport modelling and implications for DEMO

Abstract: The edge plasma of four devices, AUG, JET, ITER and a prototypical DEMO near ignition, is modelled with B2-EIRENE with a linear neutral model, carbon impurity, and variable throughput and scrape-off layer power. The scaling from ITER to DEMO is quantified as a power law scaling in device size, and JET and AUG simulations are compared to this scaling. Compared to ITER at the same scrape-off layer power per unit device volume and the same operating point relative to the edge-based density limit, edge helium dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 6 publications
1
41
0
Order By: Relevance
“…The plasma contains ions and atoms of D (representing both D and T), He, and C, as well as D 2 molecules. The present paper extends the previous simulations by a) updating the scaling of the edge parameters (from that of [2]) for variations of DT flux and helium density and flux with pumping speed and neutral pressure, b) removing carbon and introducing seed neon impurity to commence simulation of the later phase of ITER operation, and c) determining the effect of the impurity seeding on the operating window of ITER following [5,6].…”
Section: Introductionmentioning
confidence: 69%
See 4 more Smart Citations
“…The plasma contains ions and atoms of D (representing both D and T), He, and C, as well as D 2 molecules. The present paper extends the previous simulations by a) updating the scaling of the edge parameters (from that of [2]) for variations of DT flux and helium density and flux with pumping speed and neutral pressure, b) removing carbon and introducing seed neon impurity to commence simulation of the later phase of ITER operation, and c) determining the effect of the impurity seeding on the operating window of ITER following [5,6].…”
Section: Introductionmentioning
confidence: 69%
“…Initial results reported in [2] with the nonlinear neutral model indicated that the DT neutral flux was higher (factor 2) and the helium density and flux at the separatrix were lower (factor 0.33) than for the less complete linear neutral model but the scaling had then not yet been determined. We have now varied both pumping speed and throughput (i.e.…”
Section: Scaling Of Edge Parametersmentioning
confidence: 99%
See 3 more Smart Citations